NOX4/H2O2/mTORC1 Pathway in Salt-Induced Hypertension and Kidney Injury. Issue 1 (July 2020) - Kumar, Vikash; Kurth, Theresa; Zheleznova, Nadezhda N.; Yang, Chun; Cowley, Allen W.
Abstract : We have reported that a high-salt (4.0% NaCl) dietary intake activates mTORC1 and inhibition of this pathway with rapamycin blunts the chronic phase of salt-induced hypertension and renal injury in Dahl salt-sensitive (SS) rats. In SS rats, high-salt intake is known to increase the renal production of H2 O2 by NOX4, the most abundant NOX isoform in the kidney, and the global knockout of NOX4 blunts salt-sensitivity in these rats. Here, we explored the hypothesis that elevations of H2 O2 by NOX4 in high-salt fed SS rat stimulate mTORC1 for the full development of salt-induced hypertension and renal injury. Our in vitro studies found that H2 O2 activates mTORC1 independent of PI3K/AKT and AMPK pathways. To determine the in vivo relevance of NOX4/H2 O2 /mTORC1 in the salt-induced hypertension, SS- Nox4 knockout (SS Nox4 −/− ) rats were daily administrated with vehicle/rapamycin fed a high-salt diet for 21 days. Rapamycin treatment of SS Nox4−/− rats had shown no augmented effect on the salt-induced hypertension nor upon indices of renal injury. Significant reductions of renal T lymphocyte and macrophage together with inhibition of cell proliferation were observed in rapamycin treated rats suggesting a role of mTORC1 independent of NOX4 in the proliferation of immune cell. Given the direct activation of mTORC1 by H2 O2 and absence of any further protection from salt-induced hypertension in rapamycin-treated SS Nox4 −/− rats, we conclude that NOX4-H2 O2 is a major upstream activator of mTORC1 that contributes importantly to salt-induced hypertension and renal injury in the SS rat model. Abstract : Supplemental Digital Content is available in the text.